Analisis pengendalian kualitas produk keripik tempe Deny menggunakan pendekatan six sigma DMAIC terintegrasi fuzzy FMEA [Analysis of the quality control of Deny's tempe chips using a six sigma DMAIC-integrated fuzzy FMEA approach] - Siti Asmaul Mustaniroh; Nadya Prabaningtias (Jurnal Teknologi & Industri Hasil Pertanian, 2022)
Deny Tempe Chips is one of the leading MSME chips products in Malang City. The tighter business competition encourages MSMEs to increase their competitive advantage through increasing production quality and minimizing production defects. The purpose of the study was to identify and analyze the factors causing defects in the production of tempeh chips. The research uses the six sigma DMAIC (define, measure, improve, analyze, control) method with fuzzy FMEA integration. The results showed that highest defect percentage as the main priority for improving the production process (CTQ) was oily tempe chips (82.04%). The processing capability of frying tempeh chips has a final yield value of 64.87%. The frying process sigma value of 1.88 was very uncompetitive  level and required process improvement. The sources of the problems in the frying process  were human factors, methods, and production facilities. The value of FRPN as the highest risk priority for tempe chips product defects was the limited number of skilled workers in the frying process that affected the number of defects in tempeh products. The corrective action strategy proposed was human resource planning to meet the needs of the SME workforce, including the provision of training, scheduling production supervision, and adding skilled workers in the production process.Keywords: product defects, Deny tempe chips, six sigma DMAIC method, quality control.